The Effect of Galactagogue Education Using Video Media on The Knowledge, Attitudes and Behaviors of Postpartum Mothers - Karo, Deliana Br; Hakimi, Moh.; Mufdlilah, Mufdlilah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: According to the Basic Health Research (RISKESDAS) data, the exclusive breastfeeding rate in Indonesia in 2022 was 67.96%. Data from 2021 indicated that Jambi Province had a rate of exclusive breastfeeding below the national average. Providing counseling to breastfeeding mothers and offering additional support through the use of galactagogues aims to enhance knowledge, attitudes, and practices among postpartum mothers to support the process of milk production. Purpose: To assess the impact of educational videos about galactagogues on the knowledge, attitudes, and behaviors of postpartum mothers. Methods: A quasi-experimental design with a pretest-posttest control group was used. Sampling was conducted using probability sampling with a systematic sampling technique based on odd-even selection, with an average sample size of 16 postpartum mothers per group. The instruments used included questionnaires for knowledge, attitudes, and behaviors, and educational videos. Data analysis employed the Wilcoxon test, Mann-Whitney test, and MANCOVA. Results: The study found significant p-values for the educational video media in pretest-posttest assessments: knowledge (p-value = 0.001), attitudes (p-value = 0.001), and behaviors (p-value = 0.002). Educational videos were found to be more effective than lecture-based media, with p-values of 0.000 for knowledge, 0.005 for attitudes, and no significant effect on behavior with a p-value of 0.137. The test MANCOVA showed that age, education, and occupation did not significantly affect changes in knowledge, attitudes, and behaviors. Conclusion: There is a significant impact of providing galactagogue education through video media on the knowledge and attitudes of postpartum mothers. Although there were changes in behavior before and after the video intervention, no significant difference was found between the video and lecture media regarding behavior. It is recommended to use video media as an educational tool in classes for pregnant and postpartum mothers, because it is more interesting, efficient, and easily accessible to mothers.